PENGEMBANGAN MODUL EDUKASI SINGLE PARENT ANAK JALANAN DIKAWASAN LAMPU MERAH MALL SKA PEKANBARU - Trymaizela, Thania; Yakub, Elni; Putra, Roby Maiva (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The objectives of this researchs to develop a single parent street children's education module in the MALL SKA Pekanbaru red light area in terms of clarity of material, systematic material, image support, matching time in the delivery of material, and completeness of the material. In this study using the lowest type of research and development which conducts research but is not followed by field testing. After many revisions and suggestions by supervisors I and II, the education module was validated by validators from two Guidance and Counseling Lecturers at Riau University and two Guidance and Counseling teachers. From the values and suggestions that have been given by the validator, the results of calculations for the clarity of the material are obtained values that fall into the clear category with a score of 3.75, for systematic aspects of the material to get a value including the systematic category with a score of 3.75, for the aspect of image support obtain a value that is categorized as very good with a score of 4, 25, for the aspect of time suitability in the delivery of material to get a value that includes a category that matches a score of 3, 75, and aspects of the completeness of the material get a value that includes a complete category with a score of 4.0. Whereas for all aspects of material assessment, the material compiled has fulfilled the expected criteria by obtaining a score of 3.90 which is included in the good category so that it is appropriate to use. The validator also provides suggestions to add verbatim to the module, add the source to the image, remove enough words with the word single parent, add goals and evaluate to the module.Keywords: Module, Education, Single Parent